MATHEMATICAL REPRESENTATION ABILITY OF MATHEMATICS EDUCATION STUDY PROGRAM STUDENTS - Ratumanan, Tanwey Gerson; Ayal, Carolina Selfisina; Tupamahu, Pieter Z (Jurnal Pendidikan Matematika (JUPITEK), 2022)
This research is descriptive because it aims to describe students' mathematical representation ability. Mathematical representation is related to ways of expressing mathematical ideas. Mathematical representation is divided into verbal, visual/pictorial, and symbolic representations. The subjects of this study were 40 new Mathematics Education study program students. Data were collected using test and interview techniques. Furthermore, the data were analyzed using descriptive and qualitative statistics. The results showed that only 10% of the students had the mathematical representation ability in the good category, 12.5% in the moderate category, 10% in the poor category, and 67,5% in the very poor category. In detail, for verbal skills, there is 2.5% in the very good category, 7.5% in the good category, 17.5% in the moderate category, 15% in the poor category, and 55% in the very poor category. For the ability of visual/pictorial representation, there is 2.5% in the very good category, 7.5% in the good category, 12.5% in the moderate category, 7.5% in the poor category, and 70% in the very poor category. Furthermore, for the symbolic representation ability, 10% is in a good category, 10% in the moderate category, 7.5% in the poor category, and 72.5% in the very poor category. Based on the classroom observation and interview, the low mathematical representation ability is caused by two main things, namely (1) relatively low prerequisite knowledge and (2) mathematics learning, which is dominated mainly by teachers; learning does not provide opportunities for students to develop mathematical representation skills